New international livestock institute applies molecular genetics to African livestock biodiversity conservation and breeding - Hanotte, Olivier H.; Teale, A.J. (1995)
The recent amalgamation of ILRAD and ILCA provides the perfect platform for an African livestock genetic characterization program. The knowledge accumulated at ILCA over the years by its scientists, their network of contacts and collaborations, and the network of contacts and collaborations established by the center with NARS are invaluable for the phenotypic and field characterization of such things as the physical traits, performance traits, population size, socio-economic value, etc. of African breeds. The advanced molecular genetic capacities of the former ILRAD provide a strong foundation for the genotypic characterization of the samples. This paper outlines ILRI's study of animal genetic resistance to diseases, genetic characterization of African cattle breeds, and discusses broad sub-Saharan bovine study and maintaining of African's bovine genetic resources.